Consumer’s brand loyalty in the fashion shopping industry on e-commerce platforms: Understanding the role of artificial intelligence efforts - Tran, Sy Nguyen; Anh, Tuan Ngo; Quynh, Nhu Le Ngoc (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of AI-driven marketing efforts on brand loyalty in the fashion e-commerce industry. The objective of the research is to understand how factors such as interaction, information, accessibility, customization, and entertainment contribute to the effectiveness of marketing strategies through brand experience, brand relationship, and brand trust, ultimately enhancing brand loyalty. To test the proposed hypotheses, a quantitative research design was employed using the Stimulus–Organism–Response (SOR) framework. Primary data were collected through surveys conducted with 383 consumers. The findings reveal that two out of the five AI-driven marketing factors - customization and information - have the most significant impact on brand experience, brand relationship, and brand trust. Among these mediators, brand experience emerges as the most influential driver of brand loyalty. The study concludes that AI-driven marketing efforts play a crucial role in building and reinforcing brand loyalty among online consumers, particularly within the context of e-commerce platforms. Practical implications are provided for enhancing customer service quality and maintaining effective customer relationships by integrating AI marketing tools into strategic marketing initiatives.